2005
DOI: 10.1002/14651858.cd004717.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Distraction techniques for schizophrenia

Abstract: Clinicians, researchers, policy makers and recipients of care cannot be confident of the effects of distraction techniques from the findings of this review. The few pioneering studies are small, short and poorly reported. Further data from already completed trials might help inform practice, but more trials do seem to be justified as some of these potentially simple techniques, even if their effect is negligible, could be widely implemented and prove more acceptable than other more intrusive treatments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…Boschi et al (2000) note that the employment of strategies to cope with psychotic symptoms may be most helpful in the early stages of the illness. Indeed, in more advanced stages of the illness, the relation between emotion-focused and problem-focused coping and symptom severity or outcomes such as quality of life has been found to be weak (Rudnick, 2001), and related strategies such as distraction may not be generally helpful (Crawford-Walker et al, 2005).…”
Section: Reactive Copingmentioning
confidence: 99%
“…Boschi et al (2000) note that the employment of strategies to cope with psychotic symptoms may be most helpful in the early stages of the illness. Indeed, in more advanced stages of the illness, the relation between emotion-focused and problem-focused coping and symptom severity or outcomes such as quality of life has been found to be weak (Rudnick, 2001), and related strategies such as distraction may not be generally helpful (Crawford-Walker et al, 2005).…”
Section: Reactive Copingmentioning
confidence: 99%
“…The distraction technique is a cognitive-behavioral approach [24,25] that is used to control emotions. This technique can distract a person's mind of stress, fear, anger, and discomfort.…”
Section: Introductionmentioning
confidence: 99%
“…These can be classified into three groups: cognitive, behavioural, or physiological (Crawford-Walker et al 2005). While Crawford-Walker et al concluded that distraction techniques were ineffective, more studies are warranted due to the fact that the studies looked at were considered short, small, and inadequately prepared.…”
Section: )mentioning
confidence: 99%
“…A distraction technique (often a part of cognitive behavioural therapy) is a strategy used for patients with schizophrenia to help deal with auditory hallucinations and/or interfering thoughts. These can be classified into three groups: cognitive, behavioural, or physiological (Crawford-Walker et al 2005). While Crawford-Walker et al concluded that distraction techniques were ineffective, more studies are warranted due to the fact that the studies looked at were considered short, small, and inadequately prepared.…”
Section: )mentioning
confidence: 99%